Chronic recurrent osteomyelitis: A surgeon's enigma. (4th January 2019) - Kudva, Adarsh; Kamath, Abhay T.; Dhara, Vasantha; Ravindranath, Vineetha
Abstract : Background: Chronic recurrent forms of osteomyelitis of the mandible with their morbid clinical course have long been considered a challenge to maxillofacial surgeons in terms of both diagnosis and treatment. Various classifications and treatments have been established through the ages to define and manage the inflammatory symptoms occurring in adults and children. This paper discusses two such entities occurring in an adult and a child, highlighting the diagnostic and treatment challenges of recurrent osteomyelitis. Methods: A thorough workup which included clinical, radiographic, blood investigations was done, followed by administration of antibiotics and anti‐inflammatory with or without surgical debridement/adjuvant therapies. Correlation of our findings and treatment plan was done with evidence‐based literature and practice. Results: Complete resolution of symptoms with radiographic evidence was achieved in both the cases. In the recurrence period, long‐term steroids, NSAIDs, antibiotics resulted in better outcomes. Conclusion: The evidence‐based protocol for osteomyelitis stresses on short inpatient stays predicated on efficient literature. Thorough clinical and radiographic evaluation with aggressive medical management and surgical intervention when necessary can result in longer symptom‐free periods. Thus understanding the disease, recurrence pattern and response to therapy is essential.